Louise the big cheese and the Ooh-la-la Charm School - Primavera, Elise (Simon & Schuster Books for Young Readers, 2011)
Louise, who wants nothing more than to be important, jumps at the chance to attend a charm school run by Claire Eclaire, who is from Paris.